Heat treatment simulation investigation on the mechanical performance of the inter-critical heated affected zone (ICHAZ) in ship plate steel weld joint. (August 2020) - Zhang, Tianyi; Liu, Wei; Yang, Yongmei; Xing, Junying; Dong, Baojun; Zhao, Yonggang; Fan, Yueming; Li, Xiaogang
Highlights: Mechanical properties of the inter-critical heated affected zone (ICHAZ) in ship plate steel weld joint were studied. Effects of distribution of microstructure and misorientation on fracture of simulated ICHAZ specimens were investigated. The defects volume fraction ( ρ ) relative to a prior austenite grain (PAG) were proposed. Abstract: Simulated ICHAZ specimens of ship plate steel (DH36) with different heat-treated durations, which represent various heat input for the actual welding process, were comprehensively studied on the tensile deformation and the fracture mode of impact toughness. The evolution of microstructure and misorientation distribution was characterized using an optical microscope (OM), electron backscatter diffraction (EBSD), transmission electron microscope (TEM). Results indicate that as the cooling duration increased, less lath bainite (LB) formed with the growth of polygonal ferrite (PF) and MA constituents which locates at grain boundary and intragranular, corresponding to a phenomenon that high angle grain boundary (HAGB) increase with the decrease of low angle grain boundary (LAGB). Compared with specimens treated with short heat treatment durations, which t8/5 includes 15s and 30s, samples treated with 75s of t8/5 exhibited higher tensile strength and ductility, which was associated with the increase of the defects volume fraction ( ρ ) relative to a prior austenite grain (PAG). Instrumented impact test results confirmed that the void coalescence formed in the crack propagation process was blocked by HAGB with high heat input, presenting a high value of ρ .